2004
DOI: 10.1111/j.1442-2050.2004.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of less invasive surgical procedures for thoracic esophageal cancer

Abstract: In order to minimize the invasiveness of the operative procedure for thoracic esophageal cancer, several procedures have been introduced since January 1997. They included: (i) perioperative use of steroids; (ii) muscle-sparing thoracotomy without costectomy; (iii) preparation of the gastric tube with preservation of sufficient blood supply; (iv) reconstruction of the alimentary tract via posterior-mediastinal route; and (v) formation of anastomosis between the remaining esophagus and the gastric tube at a loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 21 publications
(40 reference statements)
1
22
0
Order By: Relevance
“…Several reports identifi ed improvements in anesthesia, surgical techniques and devices, and postoperative care as factors that have reduced postoperative morbidity and mortality [10][11][12]. These factors have contributed to improved survival rates in elderly patients with esophageal cancer.…”
Section: Survival In Elderly Patientsmentioning
confidence: 98%
“…Several reports identifi ed improvements in anesthesia, surgical techniques and devices, and postoperative care as factors that have reduced postoperative morbidity and mortality [10][11][12]. These factors have contributed to improved survival rates in elderly patients with esophageal cancer.…”
Section: Survival In Elderly Patientsmentioning
confidence: 98%
“…For the improvement of long‐term survival, it is essential to minimize mortality by optimizing surgical techniques and perioperative care 17, 18, 19. In addition, severe infections, pulmonary complications, and liver dysfunction require extended intensive care and long hospital stays for some patients 9, 20.…”
Section: Introductionmentioning
confidence: 99%
“…The included studies reported on a variety of eight cancer types: pancreatic adenocarcinoma [19,28], non-small-cell lung cancer [20,23,34], ovarian [21], rectal [22,33], colorectal [25,31], endometrial [26], oesophageal [27,29,30,32], and breast cancer [24]. Sample sizes range from 37 [27] to 2628 [24] patients and the follow-up periods from six months to ten years. The glucocorticoid exposures ranged from a single administration of low dose dexamethasone to repetitive very high doses of methylprednisolone.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%